Pengaruh Transparansi Anggaran Pembangunan Infrastruktur Publik terhadap Kepatuhan Wajib Pajak Bumi dan Bangunan di Kota Medan - Siti Alyfia Astiza Batubara; Zoraya Alfathin Rangkuti (Journal of Research and Development on Public Policy, 2026)
The city of Medan allocated 45.19 percent of its regional budget (APBD) for public infrastructure in 2025; however, Land and Building Tax (PBB-P2) revenue achievement remained below the target during 2021–2025, with the lowest realization reaching 66.47 percent in 2023. This gap between high infrastructure budget allocation and low taxpayer compliance encouraged this study to examine the role of budget transparency in connecting the government and taxpayers. This study uses a quantitative approach through a survey method involving 221 property taxpayers across 21 subdistricts in Medan City. Simple linear regression analysis was applied to examine the effect of public infrastructure development budget transparency on taxpayer compliance. The instruments showed high reliability with Cronbach’s Alpha values above 0.98. The results indicate that public infrastructure budget transparency has a positive and significant effect on property tax compliance (β = 0.834; t = 22.368; sig. = 0.000), explaining 69.6 percent of compliance variation, while 30.4 percent is influenced by other factors. These findings confirm that budget transparency is a key predictor of taxpayer compliance. The Medan City Government is recommended to improve post-project budget accountability reporting as the weakest transparency indicator.